2000
DOI: 10.1080/01650250050118367
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on teacher ratings of the Child Behavior Checklist

Abstract: The knowledge we have of childhood and adolescent behaviour is, to some extent, a function of the unique perspective of the rater. Although many behavioural genetics studies have used parent and child self-reports in their assessments of child and adolescent adjustment, few have included teacher ratings of behaviour. It is possible that genetic and environmental contributions to teacher reports are different from those using parent and self-reports. The present study examined genetic and environmental influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
4

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 28 publications
(59 reference statements)
2
30
4
Order By: Relevance
“…In the literature on AP and HI, contradictory findings are reported with respect to the presence of contrast effects in parental ratings. Significant contrast effects on AP and/or HI have been reported in some studies (Simonoff et al 1998;Kuntsi and Stevenson 2001;Vierikko et al 2004;Eaves et al 1997Eaves et al , 2000, but not in others (Kuntsi et al 2005;Martin et al 2002, Thapar et al 2000, Towers et al 2000, and Hudziak et al 2000. In teacher ratings, contrast effects are absent (Simonoff et al 1998;Kuntsi and Stevenson 2001;Vierikko et al 2004;Eaves et al 1997).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the literature on AP and HI, contradictory findings are reported with respect to the presence of contrast effects in parental ratings. Significant contrast effects on AP and/or HI have been reported in some studies (Simonoff et al 1998;Kuntsi and Stevenson 2001;Vierikko et al 2004;Eaves et al 1997Eaves et al , 2000, but not in others (Kuntsi et al 2005;Martin et al 2002, Thapar et al 2000, Towers et al 2000, and Hudziak et al 2000. In teacher ratings, contrast effects are absent (Simonoff et al 1998;Kuntsi and Stevenson 2001;Vierikko et al 2004;Eaves et al 1997).…”
Section: Discussionmentioning
confidence: 79%
“…With respect to teacher ratings, it is often the case that correlations are higher in children rated by the same teacher than correlations in children rated by different teachers (Saudino et al 2005;Vierikko et al 2004;Towers et al 2000;Simonoff et al 1998; but not in Sherman et al 1997). Higher correlations in children rated by the same teacher than in children rated by different teachers, suggest that teacher rater bias plays a role.…”
Section: Introductionmentioning
confidence: 94%
“…In Finnish culture, twin children are usually placed in the same classrooms; in this study, initially 87% of the co-twins were in the same class. Earlier research has found larger twin correlations for cotwins rated by the same teacher than for those rated by separate teachers (Simonoff et al, 1998;Towers et al, 2000). As Simonoff et al (1998) have found, teachers may have difficulties in attributing behavior to a correct twin because of confusing the twins with each other.…”
Section: Sibling Effect/rater Biasmentioning
confidence: 93%
“…Twin studies using teacher data in older children (age 12 to 14 years) showed the same pattern (Simonoff et al, 1998;Towers et al, 2000;Vierikko et al, 2004). An explanation for the high resemblance in twins rated by the same teacher is that these ratings include teacher-specific influences.…”
Section: Discussionmentioning
confidence: 73%
“…From genetic studies using teacher data in older twin samples, we know that twin correlations can be much higher for twin pairs rated by the same teacher than for twin pairs rated by different teachers (Derks et al, 2005;Simonoff et al, 1998;Towers et al, 2000;Vierikko et al, 2004). According to Simonoff et al (1998) and Derks et al (2005), these high twin correlations are not due to twin confusion (i.e., the teacher confuses the members of a twin pair) but are likely to be associated with teacher and classroom characteristics.…”
mentioning
confidence: 99%